2019
DOI: 10.1136/neurintsurg-2019-015221
|View full text |Cite
|
Sign up to set email alerts
|

Effects of first pass recanalization on outcomes of contact aspiration thrombectomy

Abstract: BackgroundFirst pass recanalization (FPR, defined as achieving a modified Thrombolysis in Cerebral Ischemia (mTICI) grade 2c/3 with a single pass of a thrombectomy device) effect has not yet been evaluated in contact aspiration thrombectomy (CAT). We evaluated FPR effect on clinical outcomes and FPR predictors in CAT.MethodsAll consecutive patients who underwent frontline CAT for anterior circulation large vessel occlusion with recanalization (mTICI 2b–3) were identified from registries at six stroke centers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 44 publications
0
23
0
1
Order By: Relevance
“…It appears that efficacious time management (door-to-puncture and puncture-to-reperfusion) increases the efficacy of the procedure. Recanalization after the first passage has been shown to increase the success of MT, also by the other authors [52][53][54][55]. Identifying the factors which influence the first-pass effect may help to optimally select the patients for MT based on pre-interventional risk factors and their possible modification options.…”
Section: Discussionmentioning
confidence: 89%
“…It appears that efficacious time management (door-to-puncture and puncture-to-reperfusion) increases the efficacy of the procedure. Recanalization after the first passage has been shown to increase the success of MT, also by the other authors [52][53][54][55]. Identifying the factors which influence the first-pass effect may help to optimally select the patients for MT based on pre-interventional risk factors and their possible modification options.…”
Section: Discussionmentioning
confidence: 89%
“…Among those, age, female gender, general anesthesia, use of BGC, and occlusion of ICA also increased the chance of complete reperfusion after first-pass thrombectomy. BGC use has been widely accepted contributing to FPE during thrombectomy procedure (7,9,13,15). One of the reasons may be decreased distal embolization and more importantly increased flow reversal.…”
Section: Discussionmentioning
confidence: 99%
“…However, some trials showed that functional independence in AIS patients is only around 50% even with a high recanalization rate of over 70% (3,6). Thrombectomy with first pass effect (FPE), an emerging new metric, is strongly correlated with improved functional outcomes (7)(8)(9)(10). Thrombectomy with FPE may have many advantages such as less vessel wall injury, lower risk of clot fragments, and decreased time to reperfusion (8,11).…”
Section: Introductionmentioning
confidence: 99%
“…9 Previously, numerous studies focused on the number of thrombectomy device passes during intravascular treatment procedures and reported that the number of thrombectomy device passes is closely related to the clinical outcome and prognosis of patients with ischemic stroke. [9][10][11][12][13][14] The most significant predictor of good prognosis was successful target-vessel recanalization. 11,15 With every additional thrombectomy device pass, the vascular recanalization rate for each individual receiving continuous thrombectomy decreases successively.…”
Section: Introductionmentioning
confidence: 99%